Analisa Problematika Yuridis yang Menghambat Kepastian Hukum bagi Kepemilikan Para Pembeli Satuan Rumah Susun Komersial - Unita Christina Winata; Mutia Kirana Aprilia (Program Studi Kenotariatan Fakultas Hukum Universitas Pelita Harapan, 2026)
The apartment is one of the results of human innovation to meet the needs of business activities and residential places, this is due to the problem of population growth from year to year which continues to increase, resulting in an increasing need for residential and business places, while the amount of land area never increases. The research problem is how the regulation of apartments in positive law in Indonesi, how is the implementation of regulations on apartments in practice, and what is the ideal apartment regulation. The research aims to understand the development of legal certainty on the ownership of commercial apartment unit buyers and to examine the content of legislation on apartments and to complete the content of the law to better guarantee legal certainty and provide legal protection to buyers and parties related to apartment ownership in society. The type of research used by the author is normative legal research. The results of the study are: first, in the context of apartment regulation, there are fundamental problems in the context of Article 43 of the Apartment Law, including weaknesses in the implementation of Law Number 11 of 2011 concerning Apartments. Second, in the context of the implementation of apartment regulation, there are problems including the issue of setting a timeline from booking fee payment to completion of certificates, the issue of regulation of Resident Associations, the issue of Construction Credit regulation and Buyer Payment regulation, and the issue of fund regulation for completion of statements and certificates. Bahasa Indonesia Abstract: Rumah susun merupakan salah satu hasil karya inovasi manusia untuk memenuhi kebutuhan akan tempat melakukan kegiatan usaha dan tempat tinggal. Permasalahan penelitian yaitu bagaimanakah pengaturan rumah susun dalam hukum positif di Indonesia, bagaimana implementasi aturan tentang rumah susun dalam praktek, dan bagaimanakah aturan rumah susun yang ideal. Tujuan penelitian adalah memahami perkembangan kepastian hukum atas kepemilikan para pembeli satuan rumah susun komersial dan mengkaji isi perundang-undangan tentang rumah susun dan melengkapi isi dari undang-undang agar lebih menjamin kepastian hukum dan memberikan perlindungan hukum kepada para pembeli dan pihak yang berkaitan dengan kepemilikan rumah susun di masyarakat. Adapun jenis penelitian yang digunakan penulis yaitu penelitian hukum normatif. Hasil penelitian adalah: pertama, dalam konteks pengaturan rumah susun terdapat masalah mendasar dalam konteks Pasal 43 UU Rumah Susun antara lain adanya kelemahan-kelemahan dalam pelaksanaan UU Nomor 11 Tahun 2011 tentang Rumah Susun. Kedua, dalam konteks implementasi pengaturan rumah susun terdapat problematika antara lain isu pengaturan jadwal (timeline) sejak pembayaran booking fee sampai dengan selesainya sertipikat, isu pengaturan Perhimpunan Penghuni, isu pengaturan Kredit konstruksi dan pengaturan Pembayaran Pembeli, serta isu pengaturan dana untuk penyelesaian pertelaan dan sertipikat.